Advanced materials and engineering : selected, peer reviewed papers from the Annual International Conference on Intelligent Materials and Nanomaterials (AIMN 14), April 18-19, 2014, Seoul, South Korea - Hin, Taufiq Yap Yun (Advanced materials research ;, 2014)
Collection of selected, peer reviewed papers from the Annual International Conference on Intelligent Materials and Nanomaterials (AIMN 14), April 18-19, 2014, Seoul, South Korea. The 90 papers are grouped as follows: Chapter 1: Advanced Materials, Technologies and Applications, Chapter 2: Nanomaterials and Nanotechnologies, Chapter 3: Composites and Alloys, Chapter 4: Manufacturing Processes, Materials Forming and Machining, Chapter 5: Power systems, Energy and Environmental Engineering, Chapter 6: Applied Mechanics and Engineering Keyword: Advanced Materials; Nanomaterials and Nanotechnologies;Composites and Alloys; Manufacturing Processes, Materials Forming and Machining; Power systems, Energy and Environmental Engineering; Applied Mechanics and Engineering Scientists and engineers present 88 papers on advanced materials, technologies, and applications; nanomaterials and nanotechnologies; composites and alloys; manufacturing processes, materials forming, and machining; power systems, energy, and environmental engineering; and applied mechanics and engineering. Among specific topics are the thermal properties of unsaturated polyester resin treated with intumescent flame retardants, micro-segregation behavior in a single crystal superalloy, a novel approach to determining the critical fracture strain of a near-alpha titanium alloy during hot compression deformation, the research status and prospects for solar hydrogen production, phonon interaction of ultrasound waves in condensed media, and analyzing the shock response of a marine gearbox. -- Materials science-- Nanomaterials-- Nanotechnology.